Morphological variability of recent species of the order Cassiduloida (Echinodermata: Echinoidea) of Mexico - Caballero-Ochoa, Andrea-Alejandra (2021)
ntroduction: In Mexico, there are two recorded living species of Cassiduloida: Cassidulus caribaearum and Rhyncholampas pacifica. Most of the taxonomic studies on cassiduloids have used external morphology, pedicellariae and morphometric characters; however, the intraspecific variation of quantitative and qualitative characters has been poorly evaluated. Objective: To compare the basic morphology of R. pacifica and C. caribaearum. Methods: We examined a total of 2 158 specimens of R. pacifica and C. caribaearum, selecting 50 to evaluate shape and size with linear regression and Principal Component analysis. We selected an additional 62 specimens per species to identify significant character correlations and morphological groups within species. Results: There is a direct relationship between Test length and Test width. Test height/Test width, and Total length (oral view)/Distance from the ambitus to the peristome apex, are the two main ratios to distinguish both species. C. caribaearum is more dorsoventrally compressed and has a round peristome base; versus R. pacifica has a tall and triangular one. There are four morphological groups of C. caribaearum and two groups for R. pacifica. Conclusions: These two species can be distinguished with reliable morphological characters, in which peristome shape suggests that R. pacifica is more adapted to burrowing deeper into certain types of substratum.